2019
DOI: 10.4103/ortho.ijortho_440_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Structural Outcomes after Arthroscopic Repair of Medium- to Massive-Sized Delaminated and Nondelaminated Rotator Cuff Tears

Abstract: Introduction: Current evidence is controversial about the outcomes after the repair of the delaminated versus nondelaminated rotator cuff tears. The objective of this study was to evaluate the factors affecting delamination of the cuff and clinical and structural outcomes after en masse arthroscopic repair of delaminated versus nondelaminated cuff of varying sizes. Materials and Methods: A total of 233 patients with full-thickness posterosuper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The full texts of the remaining 24 articles were further assessed, resulting in the exclusion of 14 articles owing to a lack of data. Finally, a total of ten studies [10, 13–16, 18, 24–27] were included (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The full texts of the remaining 24 articles were further assessed, resulting in the exclusion of 14 articles owing to a lack of data. Finally, a total of ten studies [10, 13–16, 18, 24–27] were included (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Data on the retear rate were reported in seven studies [10, 14–16, 18, 26, 27], and median heterogeneity was observed across the included studies ( I 2 = 60.6%). In the assessment of potential publication bias, the Harbord test was employed on the binary variable “retear.” The resulting P value showed no significant difference from zero, indicating an absence of publication bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations